Encephalic death. ¿life or death? Ethic aspects. - Ariel Uriarte Méndez; Jesús Vila Díaz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
In this work a historical approach is made about the determination of death. Here is exposed how man has looked for objective criteria that allow him to state when a person has definitely died. A revision is made about the evolution of these criteria until reaching encephalic death, clinical situation that comes to light as a consequence of the intensive care development and that asks for a safe and opportune recognition due to its importance for organs donation. The encephalic death is considered by the scientific community as the subject's death, which is supported by legislation of most countries including Cuba. This work offers data demonstrating that the criteria to define the irreversibility of encephalic functions, are safe. It is analyzed how the lack of unanimity of doctors to withdraw the assistance to a patient with encephalic death and declare him dead, shows the complexity of the theme in the sense that it implies an ethic problem. This is linked to the incomprehensible it may result to the family that a relative be dead having cardiac function. It is concluded that the concept of death is also sociocultural and that it has to be considered at the time of debating about the intensive care assistance withdrawal to a patient with encephalic death.